Catalogue of Pyrgotidae (Diptera: Tephritoidea) from Chile - González-Aravena, Christian Raúl; Mello, Ramon Luciano; Elgueta -Donoso, Mario Elgueta Donoso (Papéis Avulsos de Zoologia, 2021)
A catalogue of the Pyrgotidae (Diptera) from Chile is provided. All valid names are presented, comprising three species in two genera for the country. All references known to us from the taxonomic and biological literature, to the included names, are provided, including information about name, author, year of publication, page number, type species, type locality, distribution, and references.